Newsprint Grade Pulps from Pinus patula - Sharma, Y. K.; Mathur, G. M.; Bahadur, Om; Dhoundiyal, S. N. (Indian Forester, 1984)
Plantations of different species of tropical pines have raised all over the country. Tropical pines can be a good raw material resource for the much wanted newsprint grade printing paper. In this paper, results on pulping of Pinus patula grown in Uttar Pradesh, by sulphate, chemi-mechanical and refiner mechanical processes have been recorded. Results show that suitable pulps in good yield can be produced by these processes. Blending studies of these three type of pulps further revealed that newsprint grade paper can be produced from Pinus potula.